PERALIHAN HAK CIPTA KEPADA AHLI WARIS MENURUT HUKUM PERDATA - Muchtar Anshary Hamid Labetubun; Sabri Fataruba (SASI, 2016)
Copyright is a proprietary right therefore is of a special nature because the right is onlygranted to the creator or owner / holder of the rights concerned for within a certain period oftime obtaining legal protection to announce, reproduce, distribute, and other works of hiswork, or grant permission to Other people to do these things. Copyright is classified as theright to movable objects, so that copyright may be transferred either wholly or partially dueto inheritance, grant, endowment, testament, written agreement, or any other cause levied inaccordance with the provisions of the law. The arrangement of the inheritance of copyrightshall be regulated in accordance with the inheritance law based on the Civil Code whichregulates the status of a person's property after passing away by means of transfer of suchproperty to another person and Law Number 28 Year 2014 concerning the Copyright thatregulates the inheritance of copyright. Copyright as an inherited property may transfer ortransfer ownership in whole or in part which takes place automatically since the death of thecopyright owner (heir) and the status of copyright after being inherited is still recognized andprotected by Law Number 28 of 2014.